Enhancement of mechanical and physical properties of electrospun PAN nanofiber membranes using PVDF particles - Elkhaldi, Raed M.; Guclu, Serkan; Koyuncu, Ismail (Elsevier BV, 2016)
AbstractIn this study, polyacrylonitrile (PAN) nanofiber mats were fabricated using electrospinning method. Three hundred nanometers of polyvinylidene fluoride (PVDF) fine particles were used to enhance the mechanical strength and structural integrity of the as-spun nanofibrous membrane. As-spun nanofibrous mats were submerged in different concentrations of PVDF dispersions to incorporate PVDF particles among PAN nanofibers matrix. Subsequently, they were subjected to post-heat treatment at 177°C. The fused PVDF cemented the strings and welded the junctions that resulted in strengthening the fibers and enhancing its bonding together. The PVDF-cemented PAN (PVDF-c-PAN) membranes were characterized by scanning electron microscopy, dynamic mechanical analysis, porometry, and permeability analysis. Results showed good improvement in the membranes’ mechanical properties in terms of tensile strength and Young’s modulus. Comparing to as-spun PAN, the average increase in Young’s modulus and tensile strength in th...